Guideline on Fitness for Work in the Steel Work Section at Bang Sai Arts and Crafts Centre under the Patronage of the Queen - Kamtanode, Karn; Sirirattanaprug, Somkeit (Journal of Health Science of Thailand, 2018)
The purpose of the crossectional study was to recommend a guideline to pre-assess fitness for work in the steel work section to train the handicapped and the underserved at Bang Sai Arts and Crafts Centre and to recommend a guideline for physical examination according to the job risks. Subjects were 8 steel workers at Bang Sai arts and crafts centre. Data were collected in a walkthrough survey to identify health hazards and an interview, followed by physical examination for workers with health problem during 3-12 January 2007. The results showed that the hazard of steel work includes metal fume, dust, heat, radiation and solvents. The most frequent accident were cut by the pieces of sharp metal, and eye injury by metal foreign body. The guideline for selecting person to fit for the task should include special considerations for those with: asthma; emphysema; hearing loss; ametropia; epilepsy; allergic dermatitis; and impairments of arm, hand and spine. The physical examination according to the job risk should include lung function test, eye sight examination and audiogram.